Asthma Microbiome Studies and the Potential for New Therapeutic Strategies - Huang, Yvonne J. (Current allergy and asthma reports, 2013)
Recent applications of culture-independent tools for microbiome profiling have revealed significant relationships between asthma and microbiota associated with the environment, gut, or airways. Studies of the airway microbiome in particular represent a new frontier in pulmonary research. Although these studies are relatively new, current evidence suggests the possibility of new therapeutic strategies for the treatment or prevention of asthma. In this article, recent literature on microbiota and asthma are critically reviewed, with a particular focus on studies of the airway microbiome. Perspectives are presented on how growing knowledge of relationships between the microbiome and asthma is likely to translate into improved understanding of asthma pathogenesis, its heterogeneity, and opportunities for novel treatment approaches.